Effect of doping concentration on avalanche multiplication and excess noise factor in submicron APD - YOU, A; CHEANG, P (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
A realistic full-band Monte Carlo (FBMC) model is applied to study the effect of doping concentration on multiplication gain and excess noise factor for electron- and hole-initiated multiplication ill thin InP p(+)-i-n(+) diodes with a range of multiplication lengths of w = 0.1 and 0.24 mu m. This model predicts a reduction in excess noise factor for both electron- and hole-initiated multiplication as the doping concentration increases. Besides dead-space effect and feedback impact ionization, the electric field profile controlled by the doping concentration significantly contributes to the fall of excess noise in submicron InP p(+)-i-n(+) diodes. (c) 2007 Elsevier Ltd. All rights reserved.